Formyl-methionine as a degradation signal at the N-termini of bacterial proteins - Konstantin I. Piatkov (Microbial Cell, 2015)
In bacteria, all nascent proteins bear the pretranslationally formed N-terminal formyl-methionine (fMet) residue. The fMet residue is cotranslationally deformylated by a ribosome-associated deformylase. The formylation of N-terminal Met in bacterial proteins is not strictly essential for either translation or cell viability. Moreover, protein synthesis by the cytosolic ribosomes of eukaryotes does not involve the formylation of N-terminal Met. What, then, is the main biological function of this metabolically costly, transient, and not strictly essential modification of N-terminal Met, and why has Met formylation not been eliminated during bacterial evolution? One possibility is that the similarity of the formyl and acetyl groups, their identical locations in N-terminally formylated (Nt-formylated) and Nt-acetylated proteins, and the recently discovered proteolytic function of Nt-acetylation in eukaryotes might also signify a proteolytic role of Nt-formylation in bacteria. We addressed this hypothesis about fMet-based degradation signals, termed fMet/N-degrons, using specific E. coli mutants, pulse-chase degradation assays, and protein reporters whose deformylation was altered, through site-directed mutagenesis, to be either rapid or relatively slow. Our findings strongly suggest that the formylated N-terminal fMet can act as a degradation signal, largely a cotranslational one. One likely function of fMet/N-degron is the control of protein quality. In bacteria, the rate of polypeptide chain elongation is nearly an order of magnitude higher than in eukaryotes. We suggest that the faster emergence of nascent proteins from bacterial ribosomes is one mechanistic and evolutionary reason for the pretranslational design of bacterial fMet/N-degrons, in contrast to the cotranslational design of analogous Ac/N-degrons in eukaryotes.